Optimasi struktur proses dan penerapan metodologi six sigma di unit NPK Phonska – PT Petrokimia Gresik - Arief Setyanto; F. Purwanto; Dwi Satrio Anurogo (Jurnal Rekayasa Proses, 2009)
PT Petrokimia Gresik has seven NPK fertilizer plants with total production capacity of two million tons per year. The existing capacity is much higher in comparison with its design capacity. An effort to increase the production capacity was done simultaneously by process optimization, equipment modifications and operational method improvement. The present work was a case study from NPK Phonska Plant II; one of the plants that has already successfully increased its capacity from 1,320 tons / day to 2,400 tons / day or 182% of its original design capacity. The process optimization resulted in reduction of reaction path and process structure. Equipment modifications were done according to the new process, meanwhile improvement ofthe operational method was done through six sigma's methodology implementation. All improvement steps were done by local engineers and technicians of PT Petrokimia Gresik andthe achievement therefore becamea pride of all constituents involved in the project. The significant improvement in fertilizer production capacity also gave large contribution to the national effort in achieving and keeping self-sufficient foodstoke.